Engineering Innate Immunology in a Humanised, Functional, In Vitro Model of Healthy Myocardium - Suku, Meenakshi (Trinity College Dublin. School of Engineering. Discipline of Mechanical & Manuf. Eng, 2024)
Cardiovascular disease stands as the leading cause of death globally, claiming approximately 19.05 million lives in 2020. On the contrary, the development of cardiovascular drugs is experiencing a decline, largely due to the complexities involved in understanding the pathophysiology of various heart diseases and assessing the effects of drugs on healthy human hearts. The development of induced pluripotent stem cell (iPSC) technology and the availability of cardiac cell types in vitro, has resulted in a surge in efforts to fabricate human cardiac models for disease modelling and drug discovery applications. Although numerous attempts evidence successful fabrication of 3 dimensional (3D) engineered heart tissues, the innate immune cell population of the myocardium ¿ particularly cardiac macrophages, are almost always overlooked. With increasing appreciation of the interactions between cardiomyocytes and macrophages in the myocardium, in this work, a 3D engineered heart tissue model of the myocardium was fabricated, with iPSC-derived cardiomyocytes (iCMs), macrophages (iMacs) and cardiac fibroblasts (iCFs), all from the same iPSC parent line. After characterising iCMs, iCFs and iMacs in depth, the conditioning of iMacs to align to a cardiac resident macrophage-like phenotype in the presence of iCMs in monolayer culture is explored. Subsequently, the effect of electrical stimulation on iCMs, iMacs and iCM/iMac co-cultures, is investigated. The 2D characterisation is translated into an engineered heart tissue model, wherein, improvement in tissue characteristics in the presence of iMacs is demonstrated. Finally, the addition of myofibroblasts (activated iCFs) into the tissues is explored, as a preliminary platform for modelling cardiac tissue fibrosis.
APPROVED
Keywords: tissue resident macrophages; cardiac macrophages; cardiac tissue engineering; engineered heart tissues; cardiomyocytes; cardiac fibroblasts; induced pluripotent stem cells; innate immune cells